Full text in PDF of the ATIKAN journal, issue of June 2013 - ATIKAN, Editor Journal (ASPENSI, 2013)
This journal was firstly published on June 1, 2011. Since June 2012 edition, it has been organized by Faculty of Education and Teacher Training UNSUR (University of Suryakancana) in Cianjur, West Java, Indonesia and published by Minda Masagi Press as one of the publishers owned ASPENSI (Association of Indonesian Scholars of History Education) in Bandung. The ATIKAN journal is published twice a year i.e. every June and December.Â